IMPLEMENTASI KARTU TANDA MAHASISWA DIGITAL BERBASIS BLOCKCHAIN - Muhammad Ihsan; Erick Irawadi Alwi; Yulita Salim (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Identity management in higher education still generally relies on physical cards and centralized systems that are vulnerable to loss, forgery, and limited independent verification. This study aims to design and implement a blockchain-based digital student identity card system that supports integrated credential issuance, verification, and revocation. The study uses the Design Science Research Methodology (DSRM) through the stages of problem identification, design, prototype development, demonstration, and evaluation. The system is built using a hybrid architecture, in which student identity data are stored off-chain, while credential hashes and revocation status are recorded on-chain through a smart contract deployed on the Polygon Amoy Testnet. Credentials are issued in the form of JWT-based Verifiable Credentials and signed using the ES256K algorithm. The test results show that the system successfully implements its main functions, namely credential issuance, verification, and revocation. Performance testing also shows that verification can be carried out without incurring gas costs and with a response time that remains feasible for practical use. Overall, the developed system is feasible to support digital student identity services with better credential integrity and easier verification.